Dysphemism Found in “Ronny Chieng: Asian Comedian Destroys America!” Movie Script - Hadi, Febby Surya; Rosita, Nur (Universitas Negeri Padang, 2023)
This research investigates the dysphemism in the movie script of “Ronny Chieng: Asian Comedian Destroys America!” This research is aimed at finding the types and the functions of dysphemism, as well as determining the influence of cultural background differences on the use of dysphemism in the movie script. Descriptive qualitative method is used in this research. The data is taken from the utterances of Ronny in the movie. Allan and Burridge (2006) theory on dysphemism is employed in this research. The findings revealed that there are 100 dysphemistic words and phrases found in the movie script. There are five types and six functions found in the utterances of Ronny Chieng. In addition, the cultural background is indeed influencing the use of dysphemism, since the researcher found parents’ terms used as curse words, which does not reflect Asian culture. Further researchers are suggested to conduct a research on dysphemism by comparing the dysphemistic words or phrases between Asian and American stand-up comedians since this research examines only analyzes one multicultural stand-up comedian.